Performance Model for Advanced Neighbor Discovery Process in Bluetooth Low Energy 5.0-Enabled Internet of Things Networks - Shan, Gaoyang; Roh, Byeong Hee (IEEE Transactions on Industrial Electronics, 2020)
The neighbor discovery process (NDP) plays a key role in Bluetooth low energy (BLE)-enabled applications. However, when a massive number of BLE devices are involved in the NDP, signal collisions become severer, which degrade the NDP performance seriously. To solve the problem, BLE 5.0 specifies some extended features such as advanced NDP (A-NDP). The previous works on the performance models for the NDP have focused on the basic NDP (B-NDP). Though some works considered the performance evaluations on A-NDP, they have done on simulations or testbed-based experiments. Likewise, so far, the performance analysis for A-NDP has been insufficient. In this article, we propose an analytical model to evaluate A-NDP performances, such as the signal collision probability, the discovery delay, the energy consumption, and so on. With the proposed analysis model, the performances of A-NDP are analyzed from the viewpoint of various operational environments for BLE-enabled Internet-of-Things services, and compared to those of B-NDP with extended features of Bluetooth 5.0. Besides, it showed that A-NDP is not always better than B-NDP, and we discuss the operational conditions where A-NDP or B-NDP operate effectively, respectively.
Keywords: Bluetooth low energies (BLE); Bluetooth low energies (BTLE); Neighbor discovery; Operational conditions; Operational environments; Performance analysis; Performance Model; Signal collisions; BLE 4.2; BLE 5.0; Bluetooth low energy (BLE); Internet of Things (IoT); neighbor discovery process (NDP)